Investigating perfectionism and subject wellbeing among college students: Stress coping strategies as a mediator - Pham, K. V.; Duong, N. T.; Pham Thi, T. D. (Obrazovanie i nauka, 2023)
Introduction . Previous studies pointed out that there is an important relationship between personality factors and an individual’s well-being. Aim . This study aims to investigate the relationships between adaptive/maladaptive perfection and subject well-being among college students. Besides, positive/avoidance stress coping strategies are used as a mediator in the relationship between adaptive/maladaptive perfectionism and subject well-being. Methodology and research methods . This study used a quantitative research method to investigate a population of college students. Questionnaires were also delivered to 350 students in colleges in Ho Chi Minh City, Vietnam. The authors used Structural Equation Modelling (SEM) via AMOS to test all the hypotheses. Results . The findings show that (1) adaptive perfectionism can positively predict subjective wellbeing through positive coping strategies and negatively predict subject well-being through avoidance coping strategies; (2) maladaptive perfectionism can negatively predict subjective well-being through positive coping strategies and positively through avoidance coping strategies; (3) adaptive/maladaptive perfectionism can directly predict subject well-being. Scientific novelty. This study gains more insights into the role of stress coping strategies as a mediator in the relationship between adaptive/maladaptive perfectionism and subject well-being among college students. Practical significance . The findings in this study suggest that teachers, mentors, and counsellors should give appropriate counselling to college students to help them obtain good learning development and physical and mental adaptation.